Improving learning performance with extra-credit optional homework - Juan Equiza-Goñi; Isabel Rodríguez-Tejedo (Revista d'Innovació i Recerca en Educació, 2025)
INTRODUCTION. Assignments are often used at college level to reinforce learning, offer practice opportunities, and encourage self-assessment. While research indicates their positive impact on student performance, their effectiveness remains controversial and some studies suggest that extrinsic incentives like extra credit may undermine intrinsic motivation. Our study contributes to this debate by examining the effects of optional extra-credit assignments on student performance on two Economics courses.